ANALISIS DETERMINAN INDEKS STABILITAS INSTITUSI KEUANGAN DI INDONESIA PERIODE TAHUN 2017: Q1-2023: Q4 - Gabriela Rantalembang; Vecky A. J Masinambow; Dennij Mandeij (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effects of Non-Performing Loans (NPL), Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Operating Costs on Operating Income (BOPO) on the Indonesian Financial Institution Stability Index. The data used is quarterly time series data from the period 2017:Q1 to 2023:Q4. The results show that the four independent variables have a positive and significant influence on the stability of financial institutions. The increase in NPLs encourages the strengthening of risk management practices and stricter regulatory responses. The high ROA allows for the formation of a larger capital buffer and increases the resilience of the institution. LDR in the optimal range reflects the effectiveness of financial intermediation and the application of prudential principles. The increase in BOPO indicates investments in infrastructure and technology that strengthen the bank's operational fundamentals. These findings have important implications for policy development in Indonesia's banking sector. For regulators, these results support a risk-based surveillance approach that considers the complex interactions between financial variables. For bank management, this study highlights the importance of balancing growth, efficiency, and prudentiality in banking operations. Further research is recommended to consider macroeconomic variables, conduct regional comparative analysis, and integrate the impact of digital transformation on financial stability.